Association between plasma B-type natriuretic peptide and anaemia in heart failure with or without ischaemic heart disease: a retrospective study. Issue 3 (4th March 2019) - Tominaga, Mitsutoshi; Kawai, Makoto; Minai, Kosuke; Ogawa, Kazuo; Inoue, Yasunori; Morimoto, Satoshi; Tanaka, Toshikazu; Nagoshi, Tomohisa; Ogawa, Takayuki; Yoshimura, Michihiro
Abstract : Objectives: Anaemia is a risk of worsening heart failure. However, anaemia sometimes remains undetected because the superficial cardiac function does not precisely reflect the adverse impact of anaemia. Plasma B-type natriuretic peptide (BNP) could be helpful in these cases. However, the direct anaemic effects on BNP remain unknown. Herein, we compared the direct effect of anaemia on BNP and left ventricular ejection fraction (LVEF) using an advanced statistical procedure. Design: A retrospective study. Setting: Secondary care (cardiology), single-centre study. Participants: The study consisted of 3756 inpatients, including 684 without ischaemic heart disease (IHD) and 3072 with IHD. Primary and secondary outcome measures: Relationship between plasma BNP levels and LVEF values. Results: A path model was constructed to simultaneously examine the adverse impact of anaemia on LVEF and plasma BNP, allowing for renal function. The path model revealed that LVEF increased in response to low haemoglobin (Hb), and the phenomenon was prominent in non-IHD (standardised regression coefficients (St.β): −0.264, p<0.001) rather than in IHD (St.β: 0.015, p=0.531). However, the response of BNP was commonly observed in both groups (non-IHD St.β: −0.238, IHD St.β: −0.398, p<0.001, respectively). Additionally, this study showed a direct link between low estimated glomerular filtration rate and high BNP independently of LVEF. Incrementally, Bayesian structural equation modelling in covariance structure analysis clearly supported this result. The scatter plots and simple regression analysis revealed that an adequate blood supply was approximately Hb 110 g/L and over in the non-IHD patients, whereas blood was not supplied in sufficient quantities even by Hb 130 g/L in patients with IHD. Conclusion: The current study demonstrated that anaemia was a substantial risk for worsening cardiac overload as estimated by plasma BNP. The anaemic response of LVEF likely changed depending on underlying cardiac disorders (IHD or not). However, the response of BNP was robustly observed.